Ideology in news report Of Malaysia’s english medium of instruction change - Saran , Kaur Gill; Yuen , Chee Keong; Stef Bolte,; Saravanan Ramiah, (Penerbit UKM, 2012)
News reports are part and parcel of the human communication system; however they cannot be taken at face value, because reporters determine the context of a piece of news by making choices in the subjects, the point of view from which they describe the issue and through the style of their reporting. This allows media to propagate ideology through their texts. As such a comparative analysis of four newspaper articles; from The Star (Malaysia), the International Herald Malaysia (international newspaper with a Malaysian edition), The Jakarta Post (Indonesia), and The Guardian (United Kingdom), reporting on the same story using Fairclough’s (1989, 1995) framework of Critical Discourse Analysis to determine the ideological meanings associated to the papers was conducted. The focus of the articles is the July 2009 announcement on the change in medium of instruction from English to Bahasa Malaysia for the teaching of Mathematics and Science in Malaysia. Even though the news agencies have access to the same information and / or facts, the analysed reports are ideologically different and shed a different light on the issue presented. The study reveals the complexity of our human communication system and it becomes visible that newspapers from different socio-cultural and political contexts interpret and report an ideologically contested issue in different ways and in so doing influence their readers’ thinking and opinion about the issue.